2014
DOI: 10.21608/jappmu.2014.70759
|View full text |Cite
|
Sign up to set email alerts
|

Using a New Protein Sources in Feeding of Ruminants 1- Effect of Feeding Different Levels of Guar Korma as a Source of Protein on the Productive Performance of Egyptian Buffaloes.

Abstract: This work aimed to use guar korma meal in concentrate feed mixture(CFM) for growing buffalo calves rations.The trial was carried out at Animal House of Animal production Research Institute and Al-Manar Company Station. Thirty male buffalo calves averaging 176.9 Kg LBW were chosen and divided into six similar groups. The groups of animals were randomly assigned to receive six experimental rations containing CFM which included guar Korma at the rate of 0, 3.3, 6.7, 10.0, 13.3 and 16.7% in rations A,B,C,D,E and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…With this respect, the feed utilization efficiency with ration D recorded 8.671, 5.946 and 0.806 kg DM, TDN and DCP per kg gain, respectively, while feed utilization with ration A as kg TDN or DCP per kg gain were the most efficient as shown in Table (4). Generally, the better feed efficiency with animals fed ration D (containing DDGs) was agreement with those reported by Etman et. al., (2014aand 2018) and El-Shinnawy et.…”
Section: Average Feed Intake Daily Gain and Feed Efficiencysupporting
confidence: 91%
“…With this respect, the feed utilization efficiency with ration D recorded 8.671, 5.946 and 0.806 kg DM, TDN and DCP per kg gain, respectively, while feed utilization with ration A as kg TDN or DCP per kg gain were the most efficient as shown in Table (4). Generally, the better feed efficiency with animals fed ration D (containing DDGs) was agreement with those reported by Etman et. al., (2014aand 2018) and El-Shinnawy et.…”
Section: Average Feed Intake Daily Gain and Feed Efficiencysupporting
confidence: 91%
“…They found that the NDF was 46% for DDGS versus 40 and 15% for undecorticated cotton seed cake and soybean meal, respectively. Also, increase in digestibility coefficients of most nutrients for ration D were found with increasing DDGS levels in CFM of ration as a source of protein (Etman et al, 2014a).…”
Section: Resultsmentioning
confidence: 87%
“…~ 121 ~ Processed guar korma is rich in carbohydrates and proteins, which makes it a great source of protein for ruminants and other animals. It is mostly fed to milking animals in order to increase the amount of milk and milk fat content, in addition to being a good feed for beef cattle (Etman et al, 2014a) [5] . The CP content of guar korma has been reported to vary from 56 to 58 percent by Saeed et al (2017) [19] , 55.8 percent by Soliman et al (2014) [18] , 52.7 percent by Nidhina and Muthukumar (2015) [15] , 50 percent by Etman et al (2014a) [5] , and 46.9 percent by Grewal et al (2014) [9] .…”
Section: Introductionmentioning
confidence: 99%
“…It is mostly fed to milking animals in order to increase the amount of milk and milk fat content, in addition to being a good feed for beef cattle (Etman et al, 2014a) [5] . The CP content of guar korma has been reported to vary from 56 to 58 percent by Saeed et al (2017) [19] , 55.8 percent by Soliman et al (2014) [18] , 52.7 percent by Nidhina and Muthukumar (2015) [15] , 50 percent by Etman et al (2014a) [5] , and 46.9 percent by Grewal et al (2014) [9] . The CP content of guar korma is influenced by the kind of germ fraction and heat treatment applied to the finished product.…”
Section: Introductionmentioning
confidence: 99%